Co-Dispersion Delivery Systems with Solubilizing Carriers Improving the Solubility and Permeability of Cannabinoids (Cannabidiol, Cannabidiolic Acid, and Cannabichromene) from Cannabis sativa (Henola Variety) Inflorescences - Anna Stasiłowicz-Krzemień; Piotr Szulc; Judyta Cielecka-Piontek (MDPI AG, 2023)
Cannabinoids: cannabidiol (CBD), cannabidiolic acid (CBDA), and cannabichromene (CBC) are lipophilic compounds with limited water solubility, resulting in challenges related to their bioavailability and therapeutic efficacy upon oral administration. To overcome these limitations, we developed co-dispersion cannabinoid delivery systems with the biopolymer polyvinyl caprolactam-polyvinyl acetate-polyethylene glycol (Soluplus) and magnesium aluminometasilicate (Neusilin US2) to improve solubility and permeability. Recognizing the potential therapeutic benefits arising from the entourage effect, we decided to work with an extract instead of isolated cannabinoids. Cannabis sativa inflorescences (Henola variety) with a confirming neuroprotective activity were subjected to dynamic supercritical CO2 (scCO2) extraction and next they were combined with carriers (1:1 mass ratio) to prepare the co-dispersion cannabinoid delivery systems (HiE). In vitro dissolution studies were conducted to evaluate the solubility of CBD, CBDA, and CBC in various media (pH 1.2, 6.8, fasted, and fed state simulated intestinal fluid). The HiE-Soluplus delivery systems consistently demonstrated the highest dissolution rate of cannabinoids. Additionally, HiE-Soluplus exhibited the highest permeability coefficients for cannabinoids in gastrointestinal tract conditions than it was during the permeability studies using model PAMPA GIT. All three cannabinoids exhibited promising blood-brain barrier (BBB) permeability (Papp higher than 4.0 × 10−6 cm/s), suggesting their potential to effectively cross into the central nervous system. The improved solubility and permeability of cannabinoids from the HiE-Soluplus delivery system hold promise for enhancement in their bioavailability.